HUBUNGAN UNSUR IKLIM DENGAN KEJADIAN PENYAKIT DEMAM BERDARAH DENGUE KOTA PEKANBARU TAHUN 1999-2008 - Bambang Bambang; Masrizal Masrizal; Rizanda Mahcmud (Jurnal Kesehatan Masyarakat Andalas, 2010)
The incident Dengue Haemorrhagic Fever (DHF) in Pekanbaru city from year 1999-2008 always happened case fluctuation. This research aim to know relationship betwen climate with occurrence of DHFin Pekanbaru city of Year 1999-2008.The designing of research is ecology study with type of Times Study series (Time Trend Study) representing study of observational analytic. The data is from secondary data of case of DHF and climate data covering temperature, dampness, rainfall, rain day and speed of wind duringyear 1999 - 2008. The processing of data done computerized and analysed with Correlation test and Regretion. Result of research indicate that strength relation betwen temperature with occurrence of DHFis weak (r = 0, 086), negativepattern and the relation which unsignificant ( p=0,348). Strength relation of dampness with occurrence of DHF is weak (r = 0,061), negative pattern and the relation which unsignificant ( p=0,510). Strength relation of rainfall with occurrence of DHFis weak (r= 0, 1 42), positivepattern and the relation which unsignificant (p=0,142). Strength relation of rain day with occurrence of DHF is weak(r = 0,056), positivepattern and the relation which unsignificant ( p=0,544). Strength of relation speed of wind with occurrence of DBD is weak (r = 0,080), negative pattern and the relation which is unsignificant ( p=0,384).From result of research can be concluded that there is no relationship between element of climate with incident of DHF. It's expected to raising illumination aboutDHFby Public Health Service, besides community activation for efforts to eliminate mosquitoporous with 3Mplus movement and mutualcooperation.